Simulation-based mastery improves nursing skills in BSc nursing students: a quasi-experimental study - Roghayeh Mehdipour -Rabori; Behnaz Bagherian; Monirsadat Nematollahi (BMC, 2021)
Abstract Background Clinical education is an essential part of nursing education. Selected clinical teaching methods influence the quality of education. Simulation-based mastery learning has been used to improve clinical skills among nursing students and may provide a novel way to enhance nursing skills. This study aimed to assess the effect of simulation-based mastery learning on the clinical skills of undergraduate nursing students from 2017 to 2019. Methods This quasi-experimental study was conducted with two groups (the control and intervention). A hundred and five students were selected by random convenience sampling, and written consent was obtained. The intervention group participated in a simulation-based mastery learning intervention, and the control group received no intervention except for traditional training. The students of both groups completed the demographic information questionnaire and the checklist before and after the intervention. The results were analyzed by SPSS version 21 and descriptive and inferential statistics. Results The results showed no significant differences between the two groups before the intervention (p> 0.05). In addition, students' performance in the intervention and control groups improved significantly at the post-test compared with the baseline (p< 0.05). Furthermore, the Cohen test implied that the simulation-based mastery model used by the intervention group was significantly more effective than the traditional training used by the control. Conclusion These findings showed that mastery learning was more effective in improving clinical skills in undergraduate nursing students. The results suggest that other nursing and health programs can be developed by implementing a mastery-based learning model.